2020
DOI: 10.21203/rs.3.rs-33024/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wearable Sensors Technology as a Tool for Discriminating Frailty Levels During Instrumented Gait Analysis

Abstract: Background: One of the greatest challenges facing the healthcare of the aging population is frailty. There is growing scientific evidence that gait assessment using wearable sensors could be used for prefrailty and frailty screening. The purpose of this study was to examine the ability of a wearable sensor-based assessment of gait to discriminate between frailty levels (robust, prefrail, and frail).Methods: 133 participants (≥ 60 years) were recruited and frailty was assessed using the Fried criteria. Gait was… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…The use of inertial sensors has emerged as a technology useful in different gait analysis studies [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. The main studies and innovations found in the literature about inertial sensing have already been reviewed in several surveys [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of inertial sensors has emerged as a technology useful in different gait analysis studies [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. The main studies and innovations found in the literature about inertial sensing have already been reviewed in several surveys [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Five further articles were identified from manual search of references of eligible studies. One paper [33] was published after the updated search but was included when discovered incidentally. Of the 40 articles reviewed, 11 were excluded (See Appendix 2).…”
Section: Literature Searchmentioning
confidence: 99%
“…One study [17] was a mixed methods design but only the objective quantitative results were included in the report. The studies were carried out in varying settings; home: n = 14 [11,17,24,[34][35][36][37][38][39][40][41][42][43][44], laboratory: n = 8 [42,[45][46][47][48][49][50][51], hospital: in-patient n = 2 [52,53], outpatient n = 2 [34,54], community centre n = 1 [55] and not specified: n = 4 [33,[56][57][58]. Participant numbers ranged from n = 30 to n = 718.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations